Fear of the unknown: Inlfuenza vaccination - Velasco Castañón, José Gerardo; Medina de la Garza, Carlos Eduardo (UANL. Facultad de Medicina, 2014)
Influenza is a major cause of morbidity and mortality; current estimates by the World Health Organization (WHO) are 3 to 5 million cases and 250,000 to 500,000 deaths worldwide every year. Most deaths associated with it occur among people age 65 or older, as well as among persons suffering a chronic debilitating disease regardless of age. The recent 2009 pandemic served to foster interest in this disease. An inactivated virus vaccine has been available since the late 1940´s but it only began to be used extensively when the influenza virus antigenic variability was taken into account. Aside from such variability, influenza viruses are capable of infecting a wide variety of vertebrates, including many avian species, both wild and domestic, thus it is essential to monitor the antigenic characteristics of influenza virus strains currently circulating, and so the vaccine formula has to be evaluated and modiied accordingly every year